CHARACTERISTICS OF GAS SHALE IN DAKEBO FORMATION, AT WAGHETE AREA - PAPUA PROVINCE - Tobing, Robert Lumban (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2015)
Dakebo Formation is found in Akimeugah Basin. The formation is interpreted as Pliocene in age and it is sedimented on alluvial fan and flood plain environment, composed by conglomerate, sandstone, sandy shale, mudstone and lignite. In megascopic view, samples of rock in this area are blackish gray. Among shale beds there are thin sandstones and limestones layers as well as remains ofbrownish to blackish plants. The organic geochemistry and maceral analyses indicate that samples of rock contain organic material with fair to very good classification as source rocks, and consist of vitrinite and liptinite macerals. The presence of vitrinite maceral is ‘rare to major’ and liptinite is ‘rare to common’. Based on the TOC analysis, abundance of the organic material is about 3.11% to 12.62% with type II and type III kerogen. T value is about 401ºC to 431ºC and Rv is 0.28% to 0.31% indicated that organic material is immature. Kerogen type II has prone to produce oil and type III has prone to produce gas.